Prophylaxis of rhesus-sensitization of pregnant women. Experience of anti-rhesus immunoglobulin Rhesogam® N using - Nail R. Nuriev; Rushania I. Gabidullina; Diana I. Galautdinova (IP Berlin A.V., 2021)
Aim. Retrospective assessment of the efficiency and safety of the anti-rhesus Rh (D) immunoglobulin Rhesogam N in preventing isoimmunization in Rh-negative women during pregnancy. Materials and methods. An analysis of medical records of 196 Rh-negative patients who received anti-Rh immunoglobulin Rhesogam N in the period 20192021 was performed. The indications for the drug were the aspiration of chorionic villi, amniocentesis and prenatal prophylaxis in women with negative level of anti-Rh antibodies and in the case of Rh-positive husbands. Results. In total, 227 doses of the anti-rhesus immunoglobulin Rhesogam N were administered, including those women who underwent invasive procedures (aspiration of chorionic villi, amniocentesis). There were no adverse events, including anaphylaxis or drug-related events. 172 rhesus-positive babies were born. No cases of hemolityc disease of the newborns were reported. Anti-Rh antibodies were not found in their mothers after childbirth. Conclusion. The study confirmed the efficacy and safety of the antiresus Rh (D) immunoglobulin Rhesogam N for the prevention of Rh isoimmunization.